2010
DOI: 10.1677/jme-09-0143
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical development and cancer: focus on SF-1

Abstract: Steroidogenic factor-1 (SF-1/Ad4-binding protein; NR5A1) is an essential regulator of tissue-specific gene expression in steroidogenic cells and of adrenogonadal development. Here, I discuss recent data in the literature showing the implication of SF-1 and the importance of its dosage not only during development but also for adrenal cortex tumorigenesis in humans and mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 68 publications
1
31
1
Order By: Relevance
“…SF-1 has been linked to adrenocortical cancer in general and to childhood adrenocortical tumors (ACTs) in particular [13]. Studies have shown that SF-1 is overexpressed in childhood ACTs compared to normal adrenal tissue [4], [5] and that in NCI-H295R cells overexpression of SF-1 leads to increased proliferation and tumor growth [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SF-1 has been linked to adrenocortical cancer in general and to childhood adrenocortical tumors (ACTs) in particular [13]. Studies have shown that SF-1 is overexpressed in childhood ACTs compared to normal adrenal tissue [4], [5] and that in NCI-H295R cells overexpression of SF-1 leads to increased proliferation and tumor growth [48].…”
Section: Resultsmentioning
confidence: 99%
“…Functionally, SF-1 is known to transcriptionally regulate the expression of genes involved in steroid hormone synthesis and cellular cholesterol homeostasis [12]. However, less is known about SF-1's mechanisms of action and target genes in proliferation and differentiation during development and cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of transcription factor SF-1 is an important factor in the pathogenesis of adrenocortical tumors (2)(3)(4)16). Transgenic overexpression of Sf-1 in mice induces the development of adrenocortical neoplastic lesions that express gonadal markers (Gata-4, Amh) (4) and are probably derived from pluripotent adrenogonadal precursor cells lying beneath the outer adrenal connective capsule, which also have the potential to differentiate into cells of gonadal stroma phenotype (termed A cells) in mouse strains susceptible to gonadectomy-induced adrenocortical tumorigenesis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high JAG1 expression correlates with longer DFS and OS in ACC ); • matrix metalloproteinase type 2 (MMP-2) contributes to mediate the process of extracellular matrix degradation by cancer cells. Overexpression of this enzyme involved in metastatic invasion is associated with reduced DFS and OS (Volante et al 2006); • staining for phospho-histone H3, a marker for mitotic cells, was shown to have a borderline correlation with OS in ACC, which was less significant than mitotic count (Duregon et al 2014a); • low expression of serum glucocorticoid kinase 1 (SGK1), an ubiquitous serine/threonine kinase regulated by growth factors, is correlated with shorter OS in ACC (Ronchi et al 2012); • Steroidogenic Factor-1 (SF-1) is a transcription factor, belonging to the nuclear receptor superfamily, that has an essential role in the development of adrenal glands and gonads (Lalli 2010). SF-1 expression is a hallmark of ACT and its higher expression levels in ACC are associated with reduced DFS and OS (Sbiera et al 2010, Duregon et al 2013b.…”
Section: Immunohistochemical Markers Improve Prognostic Assessment Inmentioning
confidence: 99%